ANALISIS UNSUR INTRINSIK CERPEN â€œDILARANG MENYANYI DI KAMAR MANDIâ€ KARYA SENO GUMIRA AJIDARMA - Nurrachman, Ilham; Wikanengsih, Wikanengsih; Mahardika, Reka Yuda (IKIP Siliwangi, 2020)
The purpose of this research is to analyze the intrinsic elements of a literary work. Literature is an essay from the results of human thoughts and feelings that arouses imagination. Literary work is a work that examines various problems of life. But in it has its own element of beauty. The type of literary work that is often read and describes a life is short stories. The short story length is very relative and in the short story it has elements that are different from other elements, the elements that are owned are the intrinsic elements. Intrinsic elements include themes, characters, plot, setting, point of view, and mandate. The method used by researchers is a qualitative descriptive method. This method aims to describe the facts in a short story. Researchers are interested in researching a short story entitled